Strategi pembelajaran biologi di kalangan pelajar sekolah menengah - Zamri Mahamod,; N Suriya N Mustapha, (penerbit ukm, 2007)
The purpose of this study is to find out the relationship between Biology learning strategies among Form 4 students with variables, namely, gender, Biology achievement level, parents educational background and household income level. Two aspects of learning strategies were examined, that are the overall learning strategy, learning strategy according to categories, namely, in the classroom learning strategies, learning strategies outside the classroom and learning strategies for examination purposes. Mainly, this is a survey research. Eighty two Form 4 students from three schools in the area of Pasir Puteh were selected as respondents. A set of questionnaire, about Biology learning strategies based on a four point Likert Scale, was given to the students. Data gathered were analysed using the t-test and One way analysis of varian ANOVA. Results showed that there were a significant relationship between Biology learning strategies and Biology achievement level, mother's educational background and household income level where gender and father's education level has no significant relationship on Biology learning strategies.